Urban public spaces in the Czech Republic - Kratochvíl, Petr (Journal of Architecture and Urbanism, 2013)
The study deals with public space both as a physical phenomenon and social phenomenon. It defines its fundamental meaning by referring to the works of sociologists Richard Sennett and Hans Paul Bahrdt: The public space offers the opportunity to meet other people, confront the differences, and at the same time it is a place where we can strengthen social solidarity and mutual respect. The study briefly mentions the development of public spaces in Czech towns at the time of communist regime. However in the first instance it shows selected current works to document the attempts to express the openness of democratic society after 1989 and the new arrangements of public spaces. Evaluation of the development during the recent years shows both positive and negative aspects: On one side it is a sensitive reconstruction of previously neglected public spaces in historical centres of towns and several completely new spaces in other town quarters, on the other side it is too strong commercialisation of these spaces, their submission to tourism, and the lack of interesting public spaces in the places of everyday life of the inhabitants and in newly developing areas of towns. The increasing interest of professional community and general public in the quality of public space, as well as attempts to make the care for public spaces a substantial part of municipal strategies in some cities give a hope for the future.